PENGARUH RISK PROFILE, EARNINGS, DAN CAPITAL TERHADAP PERTUMBUHAN LABA - EKA ANDRIYANTI URAN, VELIKCIA; WURYANI, ENI (Jurnal Akuntansi AKUNESA, 2018)
The growth of Indonesian banking has slowed down since 2010. This makes the government need to take various actions to save and nourish banks so that they do not participate in their performance. This study aims to provide empirical evidence regarding the effect of risk profile, earnings, and capital on earnings growth. The population in this study were all banking companies in Indonesia and in determining the sample using purposive sampling technique. The sample in this study was banks that had gone public and listed their shares on the Indonesia Stock Exchange in the 2014-2015 period, which were 129 samples. The results obtained that the risk profile that is proxied by using NPL and capital that is proxied by using CAR affect earnings growth, and earnings proxied by using ROA do not affect earnings growth.Keywords: risk profile, earning, capital, profit growth